Language Assessment Literacy of Teachers - Weng, Fanrong; Shen, Bin (Frontiers in Psychology, 2022)
Language assessment literacy (LAL) is a significant component of language teachers’ expertise but is also a challenging task for most language teachers. To date, there have been relatively few studies examining the research on teachers’ LAL during these decades. To fill this void, this article reviews the conceptualizations of LAL and relevant empirical studies published from 1991 to 2021. It first analyzes various conceptualizations of LAL. Then in examining the empirical studies on teachers’ LAL, five major themes emerge: (i) teachers’ LAL levels; (ii) factors influencing LAL; (iii) language teachers’ assessment training needs; (iv) language assessment training courses; and (v) LAL development through reflection. Finally, future research directions on teachers’ LAL are discussed.